2008
DOI: 10.1002/ardp.200800009
|View full text |Cite
|
Sign up to set email alerts
|

The Development of HKI‐272 and Related Compounds for the Treatment of Cancer

Abstract: The development of HKI-272 and EKB-569 for the treatment of cancer is described. These compounds function as irreversible inhibitors of some members of the ErbB family of receptor tyrosine kinases. In particular, they target epidermal growth factor receptor (EGFR, also known as ErbB-1) and human epidermal growth factor receptor-2 (HER2, also known as ErbB-2). Both, HKI-272 and EKB-569 are 4-anilino-3-cyano quinoline derivatives that contain a 4-(dimethylamino)crotonamide Michael-acceptor group at the 6-positio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
121
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(122 citation statements)
references
References 53 publications
1
121
0
Order By: Relevance
“…15 Visual analysis of the kinases identified as having one or more cysteines in the active site based on work by Gray and coworkers 22 led to the merging of four groups into a single one (Table I). Furthermore, for Group 3F, which contains EGFR and BTK that are being targeted with covalent inhibitors, 26,27 we identified another kinase that based on structural overlays should be a member of this group. To the best of our knowledge, MAP2K7 has not been identified as being a member of this group until now.…”
Section: Discussionmentioning
confidence: 99%
“…15 Visual analysis of the kinases identified as having one or more cysteines in the active site based on work by Gray and coworkers 22 led to the merging of four groups into a single one (Table I). Furthermore, for Group 3F, which contains EGFR and BTK that are being targeted with covalent inhibitors, 26,27 we identified another kinase that based on structural overlays should be a member of this group. To the best of our knowledge, MAP2K7 has not been identified as being a member of this group until now.…”
Section: Discussionmentioning
confidence: 99%
“…One of the strategies widely used in cancer and TB therapy is targeting DNA with small molecules, imidazole/benzimidazole, and pyridine/quinoline derivatives being leading structures in this respect [anticancer [5][6][7][8][9][10] , anti-TB [11][12][13][14][15] ]. In previously research work, we successfully identify azaheterocycles derivatives (imidazole/benzimidazole and pyridine/quinoline included) with anticancer 9,10,[16][17][18][19] and anti-TB [15][16][17][20][21][22][23] activity.…”
Section: Design and Biological Activitymentioning
confidence: 99%
“…3,4 It is well known from the literature [1][2][3][4] that imidazole (and its benzo-derivative benzimidazole) and pyridine (and its benzoderivative quinoline) derivatives are core scaffolds widely present in many classes of drugs (of natural or synthetic origin), displaying a large variety of interesting biological activities (antimicrobials, antifungus, anti-inflammatory, antihypertensive, antineuropathic, antihistaminic, etc. ; anticancer [5][6][7][8][9][10] and anti-TB 11-15 also included). Encouraged by the above considerations and in continuation of our research in the area of novel anticancer 9,10,[16][17][18][19] and anti-TB [15][16][17][20][21][22][23] derivatives with azaheterocyclic skeleton, we report here the design, synthesis, structure, and in vitro anticancer and antimycobacterial activity of new hybrid imidazole (benzimidazole)/pyridine (quinoline) derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent Phase I and II studies, conducted in breast and lung adeno carcinoma, this toxicity proved to be excessive resulting in a dose of 240 mg daily being carried forward into more advanced clinical studies [194][195][196][197]. Pelitinib (EKB-569) is another analog of established dual HER1 and HER2 inhibitors [198,199]. Preclinical and Phase I studies suggest that pelitinib has greater activity in inhibiting EGFR/HER1, is capable of overcoming resistance to other EGFR-targeted TKIs due to acquired mutations, and also inhibits signaling through HER2/neu [198][199][200].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%
“…Pelitinib (EKB-569) is another analog of established dual HER1 and HER2 inhibitors [198,199]. Preclinical and Phase I studies suggest that pelitinib has greater activity in inhibiting EGFR/HER1, is capable of overcoming resistance to other EGFR-targeted TKIs due to acquired mutations, and also inhibits signaling through HER2/neu [198][199][200]. Phase I studies have been reported establishing a maximum-tolerated dose of 75 mg/day with gastrointestinal toxicity (diarrhea) being limiting [200][201][202][203][204].…”
Section: Tyrosine Kinase Inhibitorsmentioning
confidence: 99%